Proti "napačnemu branju" - Virk, Tomo (Primerjalna književnost, 2001)
Against "cultural misreading". - The author attempts to show the boundaries of the non-critical practice of pluralistic interpretations of Márquez novel One Hundred Years of Solitude. Although the novel itself offers a key for "mythological" reading, it is usuallz read as a post-modernist or meta-fictional work. Such cultural misreading can be avoided through a heightened hermeneutic consciousness.
Keywords: literarna interpretacija; literarna veda; literary science; metafikcija; García Márquez, Gabriel: Sto let samote